"Sæt mig ikke paa en hardere Prøve!" Johan Kulstads beretning fra Svalbard 1853 - Knutsen, Nils Magne (University of Tromsø, 2012)
In his book from 1865 Johan Kulstad tells the story of a hunting expedition to Spitzbergen in 1853. The mother ship disappears, and in desperation Kulstad and his six men starts rowing their small hunting boat back to Norway. After six days of incredible suffering, they are rescued by a Danish ship a few miles off the coast of Finnmark. After outlining the main sides of this story, the article comments briefly on the way Kulstad tells his story: There is a mixture of pre-realistic and naturalistic narrative, there is a mixture of genres, and the text is without the heroism which is so prevalent in later Arctic narrative. Interesting detail: The way a Sami member of the expedition is portrayed.